Relationship between motion, using the GaitSmartTM system, and radiographic knee osteoarthritis: an explorative analysis in the IMI-APPROACH cohort. (25th December 2020) - van Helvoort, Eefje M; Hodgins, Diana; Mastbergen, Simon C; Marijnissen, Anne Karien; Guehring, Hans; Loef, Marieke; Kloppenburg, Margreet; Blanco, Francisco; Haugen, Ida K; Berenbaum, Francis; Lafeber, Floris P J G; Welsing, Paco M J
Abstract: Objectives: To assess underlying domains measured by GaitSmart TM parameters and whether these are additional to established OA markers including patient reported outcome measures (PROMs) and radiographic parameters, and to evaluate if GaitSmart analysis is related to the presence and severity of radiographic knee OA. Methods: GaitSmart analysis was performed during baseline visits of participants of the APPROACH cohort ( n = 297). Principal component analyses (PCA) were performed to explore structure in relationships between GaitSmart parameters alone and in addition to radiographic parameters and PROMs. Logistic and linear regression analyses were performed to analyse the relationship of GaitSmart with the presence (Kellgren and Lawrence grade ≥2 in at least one knee) and severity of radiographic OA (ROA). Results: Two hundred and eighty-four successful GaitSmart analyses were performed. The PCA identified five underlying GaitSmart domains. Radiographic parameters and PROMs formed additional domains indicating that GaitSmart largely measures separate concepts. Several GaitSmart domains were related to the presence of ROA as well as the severity of joint damage in addition to demographics and PROMs with an area under the receiver operating characteristic curve of 0.724 and explained variances (adjusted R 2 ) of 0.107, 0.132 and 0.147 for minimum joint space width, osteophyte area and mean subchondral bone density, respectively. Conclusions: GaitSmart analysis provides additional information over established OA outcomes. GaitSmart parameters are also associated with the presence of ROA and extent of radiographic severity over demographics and PROMS. These results indicate that Gaitsmart TM may be an additional outcome measure for the evaluation of OA.